Downcycling versus recycling of construction and demolition waste: Combining LCA and LCC to support sustainable policy making. (May 2018) - Di Maria, Andrea; Eyckmans, Johan; Van Acker, Karel
Graphical abstract: Highlights: LCA & LCC combination provided key elements for sustainable waste policy-making. High grade recycling can be more sustainable than low grade recycling. Transports distances and price of recycled aggregates are the main environmental and economic drivers. The most sustainable solution can be the one with highest economic cost. Abstract: Urgent solutions are needed in Europe to deal with construction and demolition waste (CDW). EU policy has contributed to significantly reducing the amount of CDW going to landfill, but most of the effort has been put in downcycling practices. Therefore, further policies are needed to stimulate high-quality recycling of CDW. The present paper presents a combined life cycle assessment (LCA) and life cycle costing (LCC) methodologies to analyse the environmental and the economic drivers in four alternative CDW end-of-life scenarios in the region of Flanders, in Belgium. The four analysed alternatives are (i) landfilling, (ii) downcycling, (iii) advanced recycling and (iv) recycling after selective demolition. LCA results show that landiflling is the scenario having the highest environmental impacts in terms of person equivalent (PE), followed by downcycling and recycling (-36%) and recycling after selective demolition (−59%). The decrease in environmental impacts is mostly due to the avoided landfilling of CDW and the recovery of materials from selective demolition. LCC results indicate that landfilling is the scenario bearing the highest total economic costs. This is due to the high landfill tax in Flanders. The recycling after selective demolition bears the second highest cost. The increase of high-quality CDW recycling can significantly reduce the overall environmental impact of the system. Implementing a high landfill tax, increasing the gate fee to the recycling plant, and boosting the sales price of recycled aggregates are the most effective drivers to facilitate a transition towards a more sustainable CDW management system. The paper demonstrates that the combined LCA and LCC results can highlight the environmental and economic drivers in CDW management. The results of the combined analysis can help policymakers to promote the aspects contributing to sustainability and to limit the ones creating a barrier.